Answer:
![v^(2)_(2)=v^(2)_(1)+(v^(2)Sin^(2)\theta )/(g^(2))](https://img.qammunity.org/2020/formulas/physics/high-school/6euci1ldeer6k19b35do34mmthl83cmco1.png)
Step-by-step explanation:
Case I:
initial velocity, u = 0 m/s
Final velocity, v' = v Sinθ /g
Height = h
acceleration = g
Use third equation of motion, we get
![v'^(2)=u^(2)+2as](https://img.qammunity.org/2020/formulas/physics/high-school/q49ewzh1vv1ik4vwd8p3o0g9639juxbfkx.png)
![\left ( (vSin\theta )/(g) \right )^(2)=0^(2)+2gh](https://img.qammunity.org/2020/formulas/physics/high-school/y08gwtg14lh25gnj1mxtsdi8clr5gh8i2o.png)
. ... (1)
Case II:
initial velocity, u = v1
Final velocity, v = v2
height = h
acceleration due to gravity = g
Use third equation of motion, we get
![v^(2)=u^(2)+2as](https://img.qammunity.org/2020/formulas/physics/high-school/obiz6wq8wm4hlxtgrpgte68bf8o00xokbq.png)
![v^(2)_(2)=v^(2)_(1)+2gh](https://img.qammunity.org/2020/formulas/physics/high-school/cbnexei0oh0tthg7jm81u0j4w72788wvbw.png)
Substitute the value of h from equation (1) ,we get
![v^(2)_(2)=v^(2)_(1)+2g(v^(2)Sin^(2)\theta )/(2g^(3))](https://img.qammunity.org/2020/formulas/physics/high-school/e6amzbezmahr2gejgruyvdh1eflwvmsn2d.png)
![v^(2)_(2)=v^(2)_(1)+(v^(2)Sin^(2)\theta )/(g^(2))](https://img.qammunity.org/2020/formulas/physics/high-school/6euci1ldeer6k19b35do34mmthl83cmco1.png)